OBTURATOR NERVE BLOCK (ONB) IN TRANSURETHRAL RESECTION OF BLADDER TUMOR (TURBT) - Muhammad Akram Malik; Saleem Nawaz (Journal of University Medical & Dental College, 2013)
ABSTRACT Background: Obturator Nerve Block (ONB) in Transurethral Resection of Bladder Tumor (TURBT) can prevent adductor reflex to avoid complications like bleeding, bladder perforation or incomplete tumor resection. ONB using anatomical land marks, use of nerve stimulator or ultrasound are various techniques of nerve block. Study Design: Prospective observational study. Material & Methods: Prospective study was conducted using ONB with anatomical land marks from 15-10-2011 to 15-07-2013. All patients of bladder tumor having mass on lateral & infero-lateral wall of bladder were included in the study. Results: Total number of patients was 53 with male to female ratio of 5:1. Average age was 55.72 years. Twenty two (41.5%), patients had two masses with size range of 1-6 cm. Duration of surgery (TURBT) was 15-30 minutes in majority (62%) of patients. Eleven patients (20.75%) required blood transfusion. Forty two (79.24%) patients were administered bilateral and 20.76% unilateral nerve block. ONB was completely successful in 90.56% cases and 9.44% has partial or incomplete block. No bladder perforation, haematoma or bruising at site of injection occurred. Conclusion: ONB with spinal anesthesia using anatomical land marks is a safe procedure with comparable success rate to the usage of nerve stimulator or ultrasonography in ONB but less time consuming. We recommend ONB in all patients of bladder tumor undergoing TURBT.